Procamallanus (Denticamallanus subgen. n.) dentatus n. sp. (Nematoda: Camallanidae) from the characid fish, Bryconops alburnoides, in the Brazilian Amazon - Morav?ec, Franti?ek Ek; Thatcher, Vernon E. (Parasite, 1997)
A new camallanid nematode, Procamallonus dentatus sp. n. is described from the intestine of the characid fish, Bryconops alburnoides Kner, 1859 from the Uburu River, Amazonas State, Brazil. The parasite is characterized mainly by the structure of the buccal capsule: four to five spiral thickenings ore present in the buccal capsule of females, while about 10 large, anteriorly directed and sharply pointed teeth are present in that of the males. This feature is used for creating a new subgenus, Denticamallanus subgen. n., with the type species P. (D.) dentatus sp. n. Other features characteristic of this species are the presence of very short (0.078-0.117 mm) spicules of equal length, 2 pairs of preanal and 3 pairs of postanal papillae and the absence of caudal aloe in the male. The tail of the female is short and wide, with a small conical appendage. The ratio of the muscular and the glandular parts of the oesophagus is 1: 1.5-1.7. A key to subgenera of the genus Procamallanus Baylis, 1923 is provided.
Keywords: Alburnoides; Aloe; Camallanidae; Characidae; Nematoda; Procamallanus